Tafsir Teologis Kepemimpinan Surat Al Maidah 51 - Oki Setiana Dewi (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2018)
Many talks on the interpretation of chapter al-Maidah verse 51 have seized the writer’s attention to rethink the meaning of the language and the context of the verse. In this article the author tries to see the textual, contextual meaning, taking into account its historical socio-psychological elements to be brought into the thematic interpretation, so that the meaning is neutral and universal. It is because the concept of leadership must combine the values of trasendental and humanist, thus opening a new paradigm of contextual understanding of sentences that can color the monotheistic vision as a peaceful Islamic face, which upholds humanist values, which see man as a creed of rahmatan lil alamin. In the constitutional review of the chapter al-Maidah verse 51, the writer sees no relation to the verse with the principal, but the psycho-social history approach implies the necessity of ethics for a leader who must have the nature of trust, to be fair and obedient to religion. So the success of a leader is not only on the side of his leadership, but how much of a good influence it can give to society and its environment.